1992
DOI: 10.1042/bj2840177
|View full text |Cite
|
Sign up to set email alerts
|

The esterolytic activity of epidermolytic toxins

Abstract: The two epidermolytic toxins were shown to have intrinsic N-t-butyloxycarbonyl-L-glutamic acid alpha-phenyl esterase activity. The activity was dependent on free toxin pKa values of 6.6 and 6.8 for ETA and ETB respectively. ETB incorporated 0.97 mol of radiolabelled di-isopropyl phosphorofluoridate/mol of protein with loss of esterolytic and epidermolytic activities. The correspondence of epidermolytic and esterolytic activities in ETA and ETB during thermal inactivation and reaction with di-isopropyl phosphor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
30
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 28 publications
1
30
0
Order By: Relevance
“…These structural similarities were most notable in the active site region known as the catalytic triad, which consists of three residues (His 72 , Asp 120 , and Ser 195 in ETA) that comprise the functional active site in a serine protease enzyme. Ser 195 and one mutant of Ser 195 (S195C, in which Ser 195 was mutated to Cys) have been studied in detail by several groups already (8,10,13). These findings contributed to the idea that ETA causes SSSS by acting directly or indirectly as an epidermal sitespecific serine protease.…”
mentioning
confidence: 81%
See 2 more Smart Citations
“…These structural similarities were most notable in the active site region known as the catalytic triad, which consists of three residues (His 72 , Asp 120 , and Ser 195 in ETA) that comprise the functional active site in a serine protease enzyme. Ser 195 and one mutant of Ser 195 (S195C, in which Ser 195 was mutated to Cys) have been studied in detail by several groups already (8,10,13). These findings contributed to the idea that ETA causes SSSS by acting directly or indirectly as an epidermal sitespecific serine protease.…”
mentioning
confidence: 81%
“…Furthermore, it has been shown that ETs have esterase activity (Ref. 13) and this study). However, protease activity has yet to be demonstrated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Protease activity has not been demonstrated for either toxin in vitro, but both ETA and ETB have intrinsic esterase activity, which is associated with serine proteases (3). Thus, it is likely that both toxins are proteases.…”
mentioning
confidence: 99%
“…It was reported that ExhA, ExhB, ExhC, ExhD, ETA and ETB show a certain similarity, exhibiting preservation of the catalytic tract of the active sites of the toxins (Ahrens & Andresen 2004). Evidence for a homologous relationship is that the catalytic triad His72, Asp120 and Ser195 of ETA align respectively with His65, Asp114 and Ser186 of ETB (Bailey & Redpath 1992). In ExhA-ExhC, His115, Asp164 and Ser239 are considered to be the catalytic triad, although the Asp164 in ExhD is replaced with a glutamate (Ahrens & Andresen 2004).…”
Section: Discussionmentioning
confidence: 99%